Strategi Penarasian Sedekah sebagai Konten di Instagram oleh Konten Kreator - Qorimah Qorimah; Retno Wahyuningsih (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
The practice of narrating almsgiving on social media also contains interesting ethical and social dimensions worth examining. On the one hand, almsgiving content on Instagram can serve as a means of preaching and inspiration, encouraging a spirit of sharing within the community. The purpose of this paper is to analyze the strategies used by content creators to narrate almsgiving as Instagram content. The research method adopted a qualitative approach. The findings indicate that content creators on the Instagram platform can employ strategies to narrate almsgiving, a form of religious-social communication. The Instagram account @sedekahsubuh.yib presents daily spirituality, while the account @kitabisacom emphasizes professionalism based on empathy. Both accounts, along with several others, share a creatively packaged message of kindness without diminishing its religious significance. The study described above reveals several strategies for narrating almsgiving on Instagram: personal narrative, spiritual narrative, and empathy narrative.